Arginine Methylation in Brain Tumors: Tumor Biology and Therapeutic Strategies - Jean-Paul Bryant; John Heiss; Yeshavanth Kumar Banasavadi-Siddegowda (Cells, 2021)
Protein arginine methylation is a common post-translational modification that plays a pivotal role in cellular regulation. Protein arginine methyltransferases (PRMTs) catalyze the modification of target proteins by adding methyl groups to the guanidino nitrogen atoms of arginine residues. Protein arginine methylation takes part in epigenetic and cellular regulation and has been linked to neurodegenerative diseases, metabolic diseases, and tumor progression. Aberrant expression of PRMTs is associated with the development of brain tumors such as glioblastoma and medulloblastoma. Identifying PRMTs as plausible contributors to tumorigenesis has led to preclinical and clinical investigations of PRMT inhibitors for glioblastoma and medulloblastoma therapy. In this review, we discuss the role of arginine methylation in cancer biology and provide an update on the use of small molecule inhibitors of PRMTs to treat glioblastoma, medulloblastoma, and other cancers.